DEVELOPMENT OF LEARNING DEVICES BASED ON PBL OF SETS MATERIAL TO FACILITATE MATHEMATICAL PROBLEM SOLVING ABILITY FOR STUDENTS IN SMP/MTs - Nur Khairunnisa; Armis; Susda Heleni (Jurnal Prinsip Pendidikan Matematika, 2022)
In the curriculum for 2013, it is proposed that one of the objectives of teaching mathematics: learners is expected to have problem-solving ability. The teacher is expected to increase the sudents activation in the learning process, especially the development of the ability to solve mathematical problems. In this context, the purpose of this study is to create produce of learning devices (syllabus, RPP and LKPD) of grade VII set material using model PBL to facilitate the ability to solve valid and practical criteria problems. The development model was used a model 4D (define, design, develop, desseminate). The research uses an instrument that is the learning device validation sheet (syllabus, RPP and LKPD). Based on data analysis, it was concluded that the problemb based mathematics learning model is valid. The results of 83% validation of the syllabus in valid categories, RPP 88% and LKPD 88% in highly valid categories. The LKPD developed was declared practical in a small group trials with an average student response 72% in practice.